Comets visitors from deep space - Eicher, David J. 1961- (Cambridge University Press, 2013)
Join David J. Eicher in this fast-paced and entertaining journey through the history, present, and future of these important yet mysterious cosmic bodies. From ancient times, humans have been fascinated by 'broom stars' and 'blazing scimitars' lighting up the sky and moving against the fixed background of stars. The Great Comets of our time still receive in-depth attention - ISON, Hale-Bopp, Hyakutake, West, and others - while recent spacecraft encounters offer amazing insight into the earliest days of the solar system. In this guide you will discover the cutting-edge science of what comets are, how they behave, where they reside, how groups of comets are related, and much more. The author carefully explores the ideas relating comets and life on Earth - and the danger posed by impacts. He finishes with practical, how-to techniques, tips, and tricks on how to successfully observe comets and even to capture your own images of them
Title from publisher's bibliographic system (viewed on 05 Oct 2015)
Keywords: Comets